Knowledge Co-Production and Social Learning on Environmental Health Issues: A Role for Interactive GIS-Based Approaches - Shrestha, R. (CRC Press, 2020)
This chapter describes two approaches we have developed for engaging stakeholders in the pro-cess of knowledge co-production and social learning related to environmental health issues. One of the approaches is called the Interactive Spatial Understanding Support System (ISUSS) that aims at supporting stakeholder dialogue during a problem understanding phase in a planning process. The other approach is called the Interactive Cumulative Burdens Assessment (Interactive-CuBA) that aims at facili-tating stakeholder dialogue in assessing cumulative burdens due to exposure to number of environmental factors in the neighbourhood. Both approaches integrate interactive GIS-based support systems that are implemented in MapTable. These approaches have been tested with stakeholders in two German cities, Dortmund and Munich. Building upon the process components and attributes for engendering social learning in a participatory activity, and the lessons learned during the development and implementation of the two approaches in Dortmund and Munich presented in this chapter, we present a conceptual frame-work for knowledge co-production and social learning by means of an interactive GIS-based approach.